Gambaran Minat dan Prestasi Belajar Mahasiswa Kedokteran Semester 2 Angkatan 2015 - Sundah, Luckyta; Opod, Henri; Pali, Cecilia (JURNAL KEDOKTERAN KOMUNITAS DAN TROPIK, 2016)
Education is something that is very important in modern society, both in terms of political, economic, and health. Interest is one of the main factors for success in the study. Interests spawned spontaneous attention that enables the creation of The concentration for a long time.The learning result is a maximum measure that has been reached by students after learning activities during the specified time. The interest in health studies program, especially in medical studies program continues to growth. Great interest has a variety of factors. This study was made to get the overview of interest and student achievement of the second semester class of Medical Faculty, University of Sam Ratulangi. This study is used descriptive methods. When collecting data is using RMIB (Rothwell Miller Interest Blank) questionnaires to get an idea of the interest and the learning achievement of the students from the second semester class of Medical Faculty, University of Sam Ratulangi. The results overview shows the interest and learning achievement (50%) of students interested in the medical with a good GPA (Grade Point Average) with the results (69.2%) of students getÂ  high GPA, (30.8%) of students get moderate GPA, and none of them obtain low GPA. It can be concluded that not all students of the second semester class of Medical Faculty, University of Sam Ratulangi interested in medical studies program, but the GPA they get still good.